Rajamangsa Mantyasih: Reconstruction of Royal Cultural Heritage as an Attraction of Gunungsari Tourist Village - Priambodo, Arya Budi; Faizah, Nafrida Imliyatul; Dangin, Bernardi S; Perez, Cristina Hoyos (CV. Austronesia Akademika, 2025)
Rajamangsa Mantyasih, a royal culinary heritage from the ancient Mataram Kingdom, is being reconstructed as a cultural attraction in Gunungsari Tourism Village, Madiun Regency, to strengthen local identity and enhance cultural-based tourism development. The purpose of this research is to explore how the historical narrative of Rajamangsa Mantyasih can be reconstructed and adapted in contemporary contexts to serve as an authentic, educational, and marketable tourism product. This study employed a descriptive qualitative approach using field observations, participatory documentation, and semi-structured interviews with cultural practitioners, community members, and tourism managers. Findings reveal that the reconstruction process integrates historical narratives from the Mantyasih Inscription with adaptive culinary practices, substituting rare ingredients with locally available resources while maintaining symbolic values. The reconstructed Rajamangsa Mantyasih is developed into two main attraction formats: the Buffet Meeting Package and the Cooking Class Package, both of which emphasize participatory and educational tourism experiences. Community involvement plays a central role, with local residents contributing knowledge, resources, and management in ways that strengthen cultural preservation and stimulate economic activities through MSMEs. The study concludes that Rajamangsa Mantyasih not only preserves historical values but also creates a sustainable cultural tourism model that promotes heritage appreciation, strengthens local identity, and contributes to community empowerment. This model offers a replicable approach for other tourism villages seeking to leverage cultural heritage as a foundation for sustainable tourism innovation.